THE INFLUENCE OF COMPETENCE AND NON-PHYSICAL WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE MEDIATED BY WORK MOTIVATION IN THE REPRESENTATIVE OFFICE OF THE FINANCIAL SUPERVISORY AND DEVELOPMENT AGENCY IN MALUKU PROVINCE - Ivansyah Ivansyah; Conchita V Latupapua; Agusthina Risambessy (SEAN Institute, 2023)
This study aims to analyze the effect of work motivation and non-physical work environment on employee performance, mediated by work motivation, on BPKP Pfovinsi Maluku employees. The research design used data analysis methods using the path paradigm with data analysis techniques using PLS-Path Modeling with the SMART PLS 3 application. The population used in this study were BPKP employees in Maluku Province with a purposive sampling technique, namely as many as 52 people. The results obtained found from this study that competence has a significant positive effect on performance, Non-Physical Work Environment has a significant positive effect on performance,